2020
DOI: 10.1002/cnr2.1222
|View full text |Cite
|
Sign up to set email alerts
|

Finding new lanes: Chimeric antigen receptor (CAR) T‐cells for myeloid leukemia

Abstract: Background: Myeloid leukemia represents a heterogeneous group of cancers of blood and bone marrow which arise from clonal expansion of hematopoietic myeloid lineage cells. Acute myeloid leukemia (AML) has traditionally been treated with multiagent chemotherapy, but conventional therapies have not improved the long-term survival for decades. Chronic myeloid leukemia (CML) is an indolent disease which requires lifelong treatment, is associated with significant side effects, and carries a risk of progression to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…have shown that the combination of anti-CD19 CAR-T-cell therapy with the TKI dasatinib can potentially provide a curative therapy option even in the phenomenon of multilinear disease with several lines of mutated cells present ( 220 ). While several studies have shown substantial success in middle- to long-term follow-up of treated patients, the current research landscape on CAR-T cells focuses on other malignancies due to the success of TKI therapy ( 221 ).…”
Section: Discussionmentioning
confidence: 99%
“…have shown that the combination of anti-CD19 CAR-T-cell therapy with the TKI dasatinib can potentially provide a curative therapy option even in the phenomenon of multilinear disease with several lines of mutated cells present ( 220 ). While several studies have shown substantial success in middle- to long-term follow-up of treated patients, the current research landscape on CAR-T cells focuses on other malignancies due to the success of TKI therapy ( 221 ).…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the family of immunotherapies which share the concept of directing the patients' immune system against the tumor by releasing breaks of immune regulation and suppression (immune checkpoint inhibition), by boosting an immune response using signaling molecules (cytokine therapy), or by infusion of adapted immune cells to optimally target and dispose the malignant cells (cellular immunotherapy, tumor-infiltrating lymphocytes, and cancer vaccine therapy) (1). Specialized T cells with CAR have proven efficacy in therapy of diverse hematopoietic and lymphatic malignancies such as leukemia (2,3), myelomas (4,5) and lymphomas (6)(7)(8). CAR-T cells are characterized by receptor proteins that have been engineered to target binding partners as specific as possible for a particular disease, for example CD19 for therapy of B cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Chronic myeloid leukemia is an indolent disease that requires lifelong treatment and affects mostly adults, while CLL as the most prevalent form of leukemia in adults accounts for onethird of all leukemias in Western countries. [11,12] The survival of patients with leukemia drastically improved in recent years as the therapeutic landscape for leukemia has significantly evolved. [13,14] However, chemoresistance and relapse due to the survival mechanisms utilized by leukemic cells are common, and leukemia is projected to account for an increased 470,000 deaths in 2040 if the current trends continue.…”
Section: Introductionmentioning
confidence: 99%